2002
DOI: 10.1023/a:1014089117419
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Frequency of Self-Mutilation in a Community Sample of Adolescents

Abstract: Currently little research exists examining self-mutilation (SM) in community samples of adolescents, despite tentative findings suggesting that self-harming behaviors, including SM may be increasing. The present study provides a comprehensive review of previous literature on the frequency of SM as well as preliminary epidemiological data concerning the frequency of SM in a community sample of high schools students. The relationship between SM, anxiety, and depressive symptomatology was also assessed. Four hund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

52
518
10
31

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 615 publications
(611 citation statements)
references
References 45 publications
52
518
10
31
Order By: Relevance
“…6,7 Rates of NSSI are notably elevated among younger people, including pre-adolescents (7.7%) 8 and adolescents (13.9% to 35.6%). [9][10][11][12][13] A recent study, using the suggested DSM-5 criteria, indicated that 6.7% of adolescents potentially qualify for a diagnosis of NSSI disorder. 12 Prevalence estimates of NSSI in clinical populations range from 12% to more than 80% in psychiatric patients.…”
Section: Limitationsmentioning
confidence: 99%
“…6,7 Rates of NSSI are notably elevated among younger people, including pre-adolescents (7.7%) 8 and adolescents (13.9% to 35.6%). [9][10][11][12][13] A recent study, using the suggested DSM-5 criteria, indicated that 6.7% of adolescents potentially qualify for a diagnosis of NSSI disorder. 12 Prevalence estimates of NSSI in clinical populations range from 12% to more than 80% in psychiatric patients.…”
Section: Limitationsmentioning
confidence: 99%
“…Rates are highest among adolescents and young adults, ranging from between 12 and 21% (Favazza 1996;Favazza et al 1989;Ross and Heath 2002;Whitlock et al 2006), with estimates of NSSI among college students being as high as 25% (Klonsky and Olino 2008).…”
Section: Prevalencementioning
confidence: 99%
“…Although NSSI is often found to be associated with depression, eating orders, and anxiety (e.g., Nock, Joiner, Gordon, Lloyd-Richardson, & Prinstein, 2006), individuals who engage in NSSI do not necessarily show evidence of these mental health concerns (Ross & Heath, 2003;Ross, Heath, & Toste, 2009), but consistently report difficulties with emotion regulation and coping with overwhelming negative feelings (Gratz & Roemer, 2004;Heath, Toste, Nedecheva, & Charlebois, 2008;Lynch & Cozza, 2009). NSSI may be used as a maladaptive coping mechanism for dealing with these negative emotions.…”
mentioning
confidence: 99%